Pediatric heart transplantation - Schweiger, Martin (J Thorac Dis, 2015)
Pediatric heart transplantation (pHTx) represents a small (14%) but very important and particular part in the field of cardiac transplantation. This treatment has lifelong impact on children. To achieve the best short and especially long-term survival with adequate quality of life, which is of crucial importance for this young patient population, one has to realize and understand the differences with adult HTx. Indication for transplantation, waitlist management including ABO incompatible (ABOi) transplantation and immunosuppression differ. Although young transplant recipients are ultimately likely to be considered for re-transplantation. One has to distinguish between myopathy and complex congenital heart disease (CHD). The differences in anatomy and physiology make the surgical procedure much more complex and create unique challenges. These recipients need a well-organized and educated team with pediatric cardiologists and intensivists, including a high skilled surgeon, which is dedicated to pHTx. Therefore, these types of transplants are best concentrated in specialized centers to achieve promising outcome.